An improved method for isolation and flow cytometric characterization of intrahepatic leukocytes from fatty and fibrotic liver tissues. Issue 5 (18th July 2022) - Kandhi, Rajani; Variya, Bhavesh; Ramanathan, Sheela; Ilangumaran, Subburaj
Abstract: Flow cytometry is an imperative tool to characterize alterations in a wide range of immune cell populations during inflammatory conditions and disease states that affect the liver such as the obesity‐induced non‐alcoholic fatty liver disease and liver fibrosis. Identification and quantification of immune cell subsets from the liver is critically dependent on efficient isolation of intrahepatic leukocytes. The isolation of leukocytes from fatty and fibrotic livers and processing the cells for flow cytometry can be challenging with respect to cell yields, purity and most importantly, the level of autofluorescence resulting from fat deposition. Here, we describe an efficient method for isolating intrahepatic leukocytes from mice fed with high fat diet and propose a strategy to alleviate autofluorescence during phenotyping by multicolor flowcytometry. We also describe a gating strategy for robust identification of granulocytes, pro‐inflammatory, anti‐inflammatory and transitional state monocyte subsets, dendritic cells, B cell, T lymphocyte subpopulations and NK cell subsets. Overall, the procedures described here will allow simultaneous processing of several samples while ensuring reproducible cell isolation and efficient noise reduction required for reliable characterization of intrahepatic leukocytes from the fatty liver tissues.